Patients with carotid intraplaque hemorrhage have higher incidence of cerebral microbleeds. (3rd October 2022) - Nardi, V; Benson, J; Saba, L; Bois, M; Meyer, F; Lanzino, G; Lilach, L; Lerman, A
Abstract: Background: Carotid intraplaque hemorrhage (IPH) is considered a strong marker of histologically defined plaque vulnerability leading to cerebrovascular ischemic events. Cerebral microbleeds (CMBs) represent hemorrhage-prone small vessel disease and they are a common finding on brain MRI in patients with cerebrovascular disease. However, the potential mechanism and the risk for CMBs are not clear. The characteristics of carotid lesions have been considered relevant in the relationship between carotid artery atherosclerosis and the presence of CMBs. The potential association between carotid IPH histologically defined and CMBs has not been investigated yet. Purpose: We have previously reported the prevalence of IPH in patients with non-obstructive carotid disease in patients who underwent carotid endarterectomy (CEA). In this study, we aimed to investigate whether the presence and the extent of carotid IPH are related to the existence of CMBs. We hypothesized that patients with carotid IPH would have a higher risk of CMBs. Methods: This retrospective study enrolled 101 consecutive patients undergoing CEA with symptomatic (including ischemic stroke, TIA, and amaurosis fugax) or asymptomatic ipsilateral carotid artery disease. Carotid plaque specimens were collected at CEA from all the patients and stained with Movat Pentachrome to identify the presence and the extent (%) of IPH. Neck CTA was obtained to measure the degree of carotid stenosis. Brain MRI was pre-surgically performed and CMBs were studied using T2*-weighted gradient-recalled echo (GRE) or susceptibility-weighted imaging (SWI) sequence. The CMBs were counted and localized. Clinical and biochemical data, comorbidities, and medications were recorded. The association between carotid IPH and CMBs was examined adjusted for other risk factors. Results: The presence of carotid IPH was in 57 (56.4%) patients. CMBs were more observed in patients with carotid IPH compared to those without IPH [19 (33.3%) vs 5 (11.4%); p=0.010]. Logistic regression analysis demonstrated an association between the extent of IPH in the carotid atheroma and the presence of CMBs [OR 1.051 (95% CI 1.012–1.090); p=0.009]. Moreover, the carotid IPH extent was associated with the number of CMBs (p=0.004). In patients with CMBs, the median degree of ipsilateral carotid stenosis was 40% (35–65%) and it was 70% (50–80%) in those without CMBs, with a significant difference between the two groups (p=0.049). Conclusions: In patients undergoing CEA, the histologically defined presence of carotid IPH and its extent are associated with CMBs on brain MR imaging. CMBs may be a potential mechanism for cerebrovascular events in patients with carotid atherosclerotic IPH and they may be an imaging marker that can distinguish the severity of the carotid artery disease. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Mayo Clinic Foundation